DOSAGE OF CISPLATIN AND RELATED TOXICITY OF CANCER PATIENTS BASED ON BODY FAT AND MUSCLE MASS - Gerina-Berzina, Aija; Vikmanis, Uldis; Bajinskis, Ainars; Purkalne, Gunta; Umbrashko, Silvija; Nakurte, Ilva; Kolesovs, Aleksandrs (European Scientific Journal, ESJ, 2015)
In oncology practice, the human body surface area (BSA) is used for the calculation of the dose of chemotherapy. The human BSA is determined by derived formulas, but it is not directly linked to the pharmacokinetics of the drugs. Obesity alters the disposition of drugs pharmacokinetics, which should be considered when prescribing medications in this patient population. Failure to adjust doses in obesity may result in increased toxicity. The aim of this study was to assess predictors of an increase in the level of trygliceride considered to be among the cardiovascular risk factors. Method. The study involved 118 oncology patients with various tumor localizations. The patients underwent anthropometric measurements (height, weight, circumference, fat fold thickness, the distance between the epicondyls above the joint), and the BSA (according to the Mosteller formula). Patients who received cisplatin chemotherapy were analyzed in serum triglyceride levels before and after the treatment. Results. A comparison of female and male subsamples revealed no significant in variance between sexes and no significant differences in initial triglyceride, triglyceride change, and in the age between groups. Body fat mass was relatively higher in females, while body muscle mass and bone mass were relatively higher in males. There was a difference in the cisplatin dose, with a higher dose for males than for females. The results demonstrate that the higher cisplatin dose and higher body fat mass are significant predictors of an increase in triglyceride for both sexes.